# Solve for y 10-(2y)/3=5

10-2y3=5
Move all terms not containing y to the right side of the equation.
Subtract 10 from both sides of the equation.
-2y3=5-10
Subtract 10 from 5.
-2y3=-5
-2y3=-5
Multiply both sides of the equation by -32.
-32⋅(-2y3)=-32⋅-5
Simplify both sides of the equation.
Simplify -32⋅(-2y3).
Cancel the common factor of 3.
Move the leading negative in -32 into the numerator.
-32⋅(-2y3)=-32⋅-5
Move the leading negative in -2y3 into the numerator.
-32⋅-2y3=-32⋅-5
Factor 3 out of -3.
3(-1)2⋅-2y3=-32⋅-5
Cancel the common factor.
3⋅-12⋅-2y3=-32⋅-5
Rewrite the expression.
-12⋅(-2y)=-32⋅-5
-12⋅(-2y)=-32⋅-5
Cancel the common factor of 2.
Factor 2 out of -2y.
-12⋅(2(-y))=-32⋅-5
Cancel the common factor.
-12⋅(2(-y))=-32⋅-5
Rewrite the expression.
-1⋅(-y)=-32⋅-5
-1⋅(-y)=-32⋅-5
Multiply.
Multiply -1 by -1.
1⋅y=-32⋅-5
Multiply y by 1.
y=-32⋅-5
y=-32⋅-5
y=-32⋅-5
Multiply -32⋅-5.
Multiply -5 by -1.
y=5(32)
Combine 5 and 32.
y=5⋅32
Multiply 5 by 3.
y=152
y=152
y=152
The result can be shown in multiple forms.
Exact Form:
y=152
Decimal Form:
y=7.5
Mixed Number Form:
y=712
Solve for y 10-(2y)/3=5

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top